2011
DOI: 10.1590/s1679-87592011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macrofauna structure in the northeast area of Todos os Santos Bay, Bahia State, Brazil: patterns of spatial and seasonal distribution

Abstract: A B S T R A C TStructure of intertidal and subtidal benthic macrofauna in the northeastern region of Todos os Santos Bay (TSB), northeast Brazil, was investigated during a period of two years. Relationships with environmental parameters were studied through uni-and multivariate statistical analyses, and the main distributional patterns shown to be especially related to sediment type and content of organic fractions (Carbon, Nitrogen, Phosphorus), on both temporal and spatial scales. Polychaete annelids account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
4
0
3
Order By: Relevance
“…was the most abundant species along the southwestern coast of India (Joydas and Damodaran 2009), in 30–50 m and in sandy, muddy or mixed bottoms, there were up to 1335 specimens per square metre. Likewise, in shallow water muddy bottoms in Bahia, Brazil an apparently undescribed species was the most abundant benthic species (Pires-Vanin et al 2011); a different species, identified as Sternaspis scutata , was the most abundant in Jiaozhou Bay, China (Wang et al 2006), and a similar condition was recorded for southern Chile (Rozbaczylo et al 2006). The study of these materials can help improve our knowledge about species variation and to facilitate their recognition as distinct species.…”
Section: Introductionmentioning
confidence: 94%
“…was the most abundant species along the southwestern coast of India (Joydas and Damodaran 2009), in 30–50 m and in sandy, muddy or mixed bottoms, there were up to 1335 specimens per square metre. Likewise, in shallow water muddy bottoms in Bahia, Brazil an apparently undescribed species was the most abundant benthic species (Pires-Vanin et al 2011); a different species, identified as Sternaspis scutata , was the most abundant in Jiaozhou Bay, China (Wang et al 2006), and a similar condition was recorded for southern Chile (Rozbaczylo et al 2006). The study of these materials can help improve our knowledge about species variation and to facilitate their recognition as distinct species.…”
Section: Introductionmentioning
confidence: 94%
“…Neste contexto, metodologias que envolvam o monitoramento de fatores naturais, juntamente com os fatores antropogênicos, são essenciais para o manejo adequado dos recursos (Pires-Vanin et al, 2011). Assim, estudos de zonação nestas regiões podem contribuir para avaliar o impacto decorrente destas atividades e para subsidiar futuros planos de manejo.…”
unclassified
“…The most abundant species in Terra Nova Bay were Tharyx cincinnatus (Ehlers 1908) and Spiophanes tcherniai Fauvel 1950 (Gambi et al 1997). In Chile Bay, M. sarsi and T. cincinnatus were the dominant species (Gallardo et al 1988), while in Todos os Santos Bay (Brazil), the most abundant species was Armandia polyophthalma Kükenthal, 1887(Pires-Vanin et al 2011.…”
Section: Discussionmentioning
confidence: 99%